Association Between Fatigue and Falls Risk Among the Elderly Aged Over 75 Years in China: The Chain Mediating Role of Falls Efficacy and Lower Limb Function - He, Yudi; Zhang, Huaguo; Song, Mi; Wu, Hongyi; Pi, Hongying (Frontiers in Public Health, 2022)
Background: Although fatigue has been shown to be strongly associated with falls risk, very few studies have focused on its mechanism involved in community-dwelling older subjects. The purpose of this study was to explore the relationship between fatigue and falls risk and its internal mechanism by constructing a chain mediation model. Methods: A cross-sectional study design was adopted. A convenience sample of 270 older adults was recruited from July to October 2021 in an urban community, in Beijing, China. The participants completed the 14-item Fatigue Scale (FS-14), Falls Efficacy Scale International (FES-I), the Short Physical Performance Battery (SPPB) and Fall-Risk Self-Assessment Questionnaire (FRQ) to measure fatigue, falls efficacy, lower limb function and falls risk. The theory of unpleasant symptoms was used as a conceptual framework. Structural equation modelling (SEM) was utilized to test the hypothetical model. Results: The overall fit of final model was found to be satisfactory: χ2/df = 1.61, CFI = 0.971, TLI = 0.962, RMSEA = 0.049 (95%CI 0.030/0.066) and SRMR = 0.023. Fatigue had a direct effect on falls risk (β = 0.559, S.E. = 0.089, 95%CI 0.380/0.731), and it also had indirect effects on falls risk (β = 0.303, S.E. = 0.072, 95%CI 0.173/0.460) through mediating factors. Falls efficacy and lower limb function were the main mediating variables, and there was a chain mediating effect (β = 0.015, S.E. = 0.010, 95%CI 0.003/0.046). Conclusions: Our study suggests that fatigue can influence falls risk among the elderly in China. There are many mediating paths between fatigue and falls risk. These results may help healthcare professionals to better understand the inherent relationship between fatigue and fall risk that may benefit older adults.